2000
DOI: 10.1007/s004250000300
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of auxin transport by aminopeptidases and endogenous flavonoids

Abstract: The 1-N-naphthylphthalamic acid (NPA)-binding protein is a putative negative regulator of polar auxin transport that has been shown to block auxin efflux from both whole plant tissues and microsomal membrane vesicles. We previously showed that NPA is hydrolyzed by plasma-membrane amidohydrolases that co-localize with tyrosine, proline, and tryptophan-specific aminopeptidases (APs) in the cotyledonary node, hypocotyl-root transition zone and root distal elongation zone of Arabidopsis thaliana (L.) Heynh. seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
293
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(314 citation statements)
references
References 45 publications
11
293
1
4
Order By: Relevance
“…In vivo studies in Arabidopsis seedlings with mutations in genes encoding flavonoid biosynthetic enzymes demonstrated a role for flavonoid regulation of auxin transport. These tt4 mutants had elevated auxin transport in young seedlings, roots, or inflorescences, consistent with the absence of an endogenous negative auxin transport regulator (Murphy et al, 2000;Brown et al, 2001;Buer and Muday, 2004;Peer et al, 2004). A comparison of the root gravitropic responses of the wild type and the chalcone synthase (CHS) null mutant, tt4(2YY6), identified a lag in gravitropic curvature in tt4(2YY6).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In vivo studies in Arabidopsis seedlings with mutations in genes encoding flavonoid biosynthetic enzymes demonstrated a role for flavonoid regulation of auxin transport. These tt4 mutants had elevated auxin transport in young seedlings, roots, or inflorescences, consistent with the absence of an endogenous negative auxin transport regulator (Murphy et al, 2000;Brown et al, 2001;Buer and Muday, 2004;Peer et al, 2004). A comparison of the root gravitropic responses of the wild type and the chalcone synthase (CHS) null mutant, tt4(2YY6), identified a lag in gravitropic curvature in tt4(2YY6).…”
mentioning
confidence: 72%
“…Reversible protein phosphorylation, which may modulate the activity, abundance, or localization of auxin transport proteins, is a second mechanism (Deruère et al, 1999;Christensen et al, 2000;Benjamins et al, 2001;Rashotte et al, 2001;DeLong et al, 2002;Friml et al, 2004). Finally, the localized synthesis of small molecules that regulate auxin transport modulates the rate of gravity response (Murphy et al, 2000;Brown et al, 2001;Buer and Muday, 2004).…”
mentioning
confidence: 99%
“…4). Amazingly, the same root regions with GUS activity accumulate both flavonoids and auxins (Murphy and Taiz, 1999;Murphy et al, 2000;Peer et al, 2001;Ljung et al, 2005). In this context, it should be stressed that, in Arabidopsis roots, ChS and chalcone isomerase (Saslowsky and Winkel-Shirley, 2001) are located in sites where the PvACCase gene promoter is active (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy that PvACCase::GUS transgene expression during development has a strong correlation to the tissues where auxins are accumulated in Arabidopsis. For example, several studies have shown high auxin concentrations in Arabidopsis hydathodes, stipules, and root tips; furthermore, flavonoids colocalize with zones of auxin accumulation (Murphy et al, 2000;Peer et al, 2001;Aloni et al, 2003). To determine auxin responsiveness of the PvACCase gene promoter, 8-dold roots were treated with IAA.…”
Section: Pvaccase Response To Exogenous Auxin Applicationmentioning
confidence: 99%
“…This is of interest because flavonols, such as quercetin and kaemferol, have been shown to inhibit plant [6,26,43] and even mammalian ABCB activities [113], and are considered to be plant endogenous auxin transport modulators or inhibitors [101,114,115].…”
Section: Imunophilins Might Mediate Auxin Transporter Sensitivity To Npamentioning
confidence: 99%